2015
DOI: 10.1371/journal.pone.0141180
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Burstein-Moss Shift and Band Gap Narrowing in Indium-Doped Zinc Oxide Thin Films

Abstract: The Burstein-Moss shift and band gap narrowing of sputtered indium-doped zinc oxide (IZO) thin films are investigated as a function of carrier concentrations. The optical band gap shifts below the carrier concentration of 5.61 × 1019 cm-3 are well-described by the Burstein-Moss model. For carrier concentrations higher than 8.71 × 1019 cm-3 the shift decreases, indicating that band gap narrowing mechanisms are increasingly significant and are competing with the Burstein-Moss effect. The incorporation of In caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(52 citation statements)
references
References 34 publications
7
38
0
Order By: Relevance
“…6b-d, the optical band gap of the films increased from 3.33; 3.32; 3.33 to 3.48; 3.47; 3.48 eV from Tauch plot, T´´ and dT/dλ plots, respectively with increasing the RF power from 100 to 200 W. T´´ is second derivative of the transmission is described as T´´(x) = [T(x + h)−2T+(x−h)]/h 2 [34]. Increasing of the band gap energy or shifting of optical absorption edge to higher energy can be explained by Burstein-Moss effect [35] due to increasing of carrier concentration with RF power. Similar behavior of the optical band gap were observed in Ref [28,33,35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6b-d, the optical band gap of the films increased from 3.33; 3.32; 3.33 to 3.48; 3.47; 3.48 eV from Tauch plot, T´´ and dT/dλ plots, respectively with increasing the RF power from 100 to 200 W. T´´ is second derivative of the transmission is described as T´´(x) = [T(x + h)−2T+(x−h)]/h 2 [34]. Increasing of the band gap energy or shifting of optical absorption edge to higher energy can be explained by Burstein-Moss effect [35] due to increasing of carrier concentration with RF power. Similar behavior of the optical band gap were observed in Ref [28,33,35].…”
Section: Resultsmentioning
confidence: 99%
“…Increasing of the band gap energy or shifting of optical absorption edge to higher energy can be explained by Burstein-Moss effect [35] due to increasing of carrier concentration with RF power. Similar behavior of the optical band gap were observed in Ref [28,33,35]. In addition a strong and sharp UV absorption edges were observed from 375 to 381 nm for prepared films.…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that surface architecture is the fundamental feature to maximize charge accumulation. Stability aspect photoelectrode potential energy barrier is minimized by doping or any means that improves carrier transport properties . Doping may shift the Fermi energy level towards conduction band edge that reduces ΔE or entropy.…”
Section: Quantum Effect: Esc Contextmentioning
confidence: 99%
“…Stability aspect photoelectrode potential energy barrier is minimized by doping or any means that improves carrier transport properties. 82,115 Doping may shift the Fermi energy level towards conduction band edge that reduces ΔE or entropy. Doping or any ways ΔE reduction shift energy level to improve, V oc or overall performance of ESC.…”
Section: Effect Of Interface Material's Functionalitiesmentioning
confidence: 99%
“…23,24 The increased optical bandgap energy is related to the increase of the carrier concentration by UV irradiation, as explained by the Burstein-Moss effect. 19,[25][26][27] Another reason for the decreased resistivity is the Al-ion doping. The amount of Al in the as-deposited film was evaluated by ICPS, confirming the presence of 1.5 ppm Al in the as-deposited film.…”
Section: Al-doped Zno Film With Citrate Ionsmentioning
confidence: 99%